APLIKASI KAMUS ISTILAH HUKUM PADA ANDROID (Information Technology and Telematics, 2014)
Abstract – The development of information technology is growing rapidly affect the lifestyle of the people in the face of problems. The use of a dictionary of legal terms that are still manual in the form of books considered less efficient in finding terms and their meanings that era, this sophisticated. Thus, the need for a dictionary of legal terms that can help people learn science in the field of law. In making the dictionary app on Android is a legal term, the author uses Prototype method, while tools used in the development of UML (Unified Modeling Language). This research has resulted in a legal term dictionary application on Android which has been used as a viable tool for the search term and the meaning of the term in the field of law. Keyword: Android, Unified Modeling Language (UML), Prototype